AOA Localization for Vehicle-Tracking Systems Using a Dual-Band Sensor Array - Al-Sadoon, Mohammed Abdullah Ghali; Asif, Rameez; Al-Yasir, Yasir Ismael Abdulraheem; Abd-Alhameed, Raed A.; Excell, Peter S. (IEEE transactions on antennas and propagation, 2020)
The issue of asset tracking in dense environments where the performance of the global positioning system (GPS) becomes unavailable or unreliable is addressed. The proposed solution uses a low-profile array of antenna elements (sensors) mounted on a finite conducting ground. A compact-size sensor array of six electrically small dual-band omnidirectional spiral antenna elements was designed as a front end of a tracker to operate in the 402 and 837 MHz spectrum bands. For the lower band, a three-element superposition method is applied to support estimation of the angle of arrival (AOA), whereas all six sensors are employed for the higher band. A low complexity and accurate AOA determination algorithm is proposed, the projection vector (PV), and this is combined with the array mentioned. Orthogonal frequency division multiplexing (OFDM) is integrated with the PV technique to increase the estimation resolution. The system was found to be suitable for installation on the roof of vehicles to localize the position of assets. The proposed system was tested for the tracking of nonstationary sources, and then two scenarios were investigated using propagation modeling software: outdoor to outdoor and outdoor to indoor. The results confirm that the proposed tracking system works efficiently with a single snapshot.